2020
DOI: 10.1371/journal.pone.0240301
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cortical activation patterns during action observation, action execution, and interpersonal synchrony between children with or without autism spectrum disorder (ASD): An fNIRS pilot study

Abstract: Engaging in socially embedded actions such as imitation and interpersonal synchrony facilitates relationships with peers and caregivers. Imitation and interpersonal synchrony impairments of children with Autism Spectrum Disorder (ASD) might contribute to their difficulties in connecting and learning from others. Previous fMRI studies investigated cortical activation in children with ASD during finger/hand movement imitation; however, we do not know whether these findings generalize to naturalistic face-to-face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 110 publications
5
42
1
Order By: Relevance
“…6 Previous fMRI and fNIRS studies have reported atypical cortical activation associated with imitation and IPS difficulties in adults and children with ASD. 13,14 However, the studies were limited to finger movements or seated reaching tasks without involving whole-body movements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 Previous fMRI and fNIRS studies have reported atypical cortical activation associated with imitation and IPS difficulties in adults and children with ASD. 13,14 However, the studies were limited to finger movements or seated reaching tasks without involving whole-body movements.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings of hyperactivation over the IPL region in children with ASD have been reported in previous fMRI and fNIRS studies involving simple finger and hand movement imitation/IPS. 13,14 The IPL region is part of the default mode network (DMN) 57 , a network that is more active during internally directed processing (i.e., mind wandering and selfreferencing), but is deactivated during externally directed processing (i.e., performing cognitively demanding tasks and goal-directed movements such as IPS). 58 DMN is important in a wide range of emotions and social functions and share similar cortical substrates including regions important for imitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, when filtering genes by ExAC scores, the analysis performed on the intersection between the clusters identified significant processes connected to observational, imitative, and vocal learning. Actually, imitation impairments in patients with ASD are typically related to their deficits in connecting and learning from others [ 61 ], and the comprehension of their interpersonal synchrony skills is now fundamental to trace the adaptive functioning and, consequently, the ASD severity, in children [ 62 ].…”
Section: Discussionmentioning
confidence: 99%